Rhodospirillum centenum, A New Growth Stimulant and Antagonistic Bacteria Against Leaf Spot of Rice Caused by Curvularia lunata - Rungrat Vareeket; Kasem Soytong (AGRIVITA, Journal of Agricultural Science, 2020)
The research objectives were to find Rhodospirillum spp. to promote plant growth and as antagonists to control leaf spot of rice. The results showed that rice var. RD41 and Pitsanulok 2 (PL2) had leaf spot caused by Curvularia lunata. R. centenum is gram negative, mobile cell motility and negative of gelatin activity test. SM41 and 61 showed glucose and lactose and/or sucrose fermentation activity, but SM72 and 92 were non-fermented activity. Isolates of R. centenum were antagonized C. lunata, a leaf spot pathogen. R. centenum expressed for ability to produce amylase, protease and lipase. R. centenum isolates SM41, SM61, SM72, and SM92 with C. lunata causing leaf spot and seed-borne fungus. In addition, the inoculated seeds var. RD 41 and Pitsanulok 2 (PL2) applied R. centenum 41, 61, 72 and 79 gave significantly better seed germination, shoot and root length. Isolate SM41 reduced disease incidence in rice var. RD41 which the disease index was on level 2 when the inoculated one was level 5. Isolate SM61 showed the disease index of level 2 but the inoculated control was level 5. It is the first report that R. centenum plays the role for growth stimulant and biological control agents against leaf spot of rice caused by C. lunata.